Tinjauan Perbedaan Kemampuan Kontrol Diri Berdasarkan Gender pada Siswa dengan Tingkat Empati Rendah - Hapsari Puspita Rini; Ni Putu Rizky Arnani; Kurrota Aini (Journal of Social, Culture, and Language, 2025)
This study aims to determine whether there are differences in self-control abilities based on gender in low empathy students. This research is a type of descriptive quantitative research that will provide an overview of a phenomenon that occurs. The population of this study were students at SMA 'X' Bangkalan with a total sample of 39 people with 16 male students and 23 female students. The sampling method was carried out using purposive sampling method by distributing empathy questionnaires to all X and XI grade students through google form media. Analysis of self-control questionnaire data filled in by the participants was carried out using an independent sample t-test technique after ensuring the distribution of normally distributed data with homogeneous data group variants. The results showed that there was no difference in the ability of self-control in male and female students who have low empathy in SMA 'X' Bangkalan. This is possible because in this study all participants had empathy in the same category and ignored the role of parenting and the role of peer groups.